Salman Rushdie’s “Unfettered Republic of the Tongue” in Fury (Philologia, 2021)
Salman Rushdie’s “Unfettered Republic of the Tongue” in Fury is an assessment of Rushdie’s achievement in this novel, which is a remarkable contribution to the contemporary literature written in English. The core argument of this essay is that Rushdie’s Fury is a novel for the new millennium by its thematic focus, setting, keen observation of various cultural aspects of contemporary America, narrative tempo and even by its suggestive dust-jacket. The mixed reception enjoyed by the novel is an aspect that reﬂects back on Fury’s potential to both irritate and elate or at least entertain. As a matter of fact, the postmodern itself has this dual potential, and Fury is just another novel in which Rushdie gives us a “nice work” of “cultural evisceration”.Fury is also an illustration in ﬁction of Baudrillard’s theory of simulacra and simulations. Rushdie’s New York is, like DeLillo’s America in White Noise, a glossy hyperreality, a simulacrum. America is real only by name, its “reality” being constantly blurred by a constant erasure of the borderline between reality and ﬁction and by the constant intrusion of the ﬁctitious into the real.To Rushdie’s mind “the unfettered republic of the tongue” is the most important of the writers’ “habitations”. This implies that a writer’s imagination has no frontiers and can never be fettered. An entertaining story-teller, Rushdie knows that stories are words invested with the power to create and restore or to destroy. In Fury words retain this double-edged potential, and the novel ends on an ambiguous note that leaves the reader in limbo.
Keywords: cultural evisceration; simulacra; simulations; glossy hyperreality; erasure of borderline; limbo